D-dimer level and Wells score in women undergone Lymphadenectomy in Gynecological Cancer to Assess Risk of Deep Venous Thrombosis - Azzo, Nawfal; D. Sulman, Safa (Journal of the Faculty of Medicine Baghdad, 2022)
Background: One of the most important prognostic indicators in cancer is the lymph node dissection. Lymphadenectomy considered as a risk factor for deep vein thrombosis in patients with gynecological malignancy who underwent surgery. D-dimer was used to detect deep vein thrombosis, thus, it’s important to predict complications of post-operative Lymphadenectomy.Objective: To predict the  risk of deep venous thrombosis by used serum D-dimer and wells score after pelvic lymphadenectomy in gynecological cancer.Patients and method:  A cross sectional study conducted in Obstetrics and Gynecology/ ward in medical city, from 1st, January 2021 to 30th, Dec. 2021. A total number of 45 (22 endometrial, 12 ovarian and 11 cervical cancers). Results: The mean±SD level of pre-operative D-dimer in patients with endometrial cancer was (423.2±123.9) while the mean±SD post-operative level was (987±125.1), the mean±SD level of pre-operative D-dimer in patients with ovarian cancer was (602±320.7) while the post-operative was (901.5± 412), mean±SD level of pre-operative D-dimer in patients with cervical cancer was (339±157) while the postoperative was (1214±327), and the mean±SD level of pre-operative D-dimer in all gynecological cancers was (541±167) while the post-operative was (1016±302). The mean±SD of wells score of those who are likely to developed DVT (n=7) in pre-operative was (2.3±0.02) while for those who are unlikely to develop deep vein thrombosis (n=38) was (2.03±0.4) with statistically significant difference (p=0.04) while highly significant difference found in pre- and post-operatively between the group of deep vein thrombosis (p˂0.001).Conclusion: Highly significant increase of post-operative D-dimer in all gynecological cancer patients.